Limiting Odour Emission from Piggery through Application of Heat Recovery System (Agricultural Engineering, 2016)
The aim of the study was to determine the effect of manure cooling by the use of the heat recovery system on odour emission from a deep litter piggery. Annual comparative research was carried out in a twin-room deep litter piggery located in Wielkopolska Voivodeship. The recovered heat was transferred to central heating and domestic hot water systems of a residential building. The study showed that the average odour emission rate from the room, where heat was recovered (0.192±0.083 ouE·s−1·kg m.c.−1) was lower than in the room without heat recovering (0.273±0.138 ouE·s−1·kg m.c.−1) (p<0.05). The difference was 27%. It was also found that there was statistically significant strong correlation (r=0.86) between the amount of the recovered heat and the percentage odour emission reduction (p<0.05). This relationship was described by the logarithmic regression line y=12.5ln(x)-21.5 (r2=0.74)